Pengaruh Financial Distress dan Audit Tenure Terhadap Audit Delay (Studi Empiris pada Perusahaan Manufaktur Sub-Sektor Consumer Non-Cyclicals yang Terdaftar di BEI Periode 2019-2024) - Pani Hikmahwati; H. M. Imam Sundarta; M. Anwar Masruri (CV. ITTC INDONESIA, 2026)
Audit Delay remains an important issue in the timeliness of corporate financial reporting, potentially reducing the relevance of information for investors and other stakeholders. Financial Distress and Audit Tenure are considered factors that may influence Audit Delay; however, prior studies have produced inconsistent findings. This study aims to analyze and provide empirical evidence regarding the effect of Financial Distress and Audit Tenure on Audit Delay in Consumer Non-Cyclicals manufacturing companies listed on the Indonesia Stock Exchange during the 2019–2024 period. This study employed a quantitative approach with a causal associative design. The population consisted of Consumer Non-Cyclicals manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2024. Using purposive sampling, 22 companies were selected, resulting in 115 observations. Secondary data were obtained from annual reports and independent auditors’ reports. Data were collected through documentation techniques and analyzed using multiple linear regression with SPSS version 26. The findings indicate that Financial Distress has no significant effect on Audit Delay. In contrast, Audit Tenure has a negative and significant effect on Audit Delay. Simultaneously, Financial Distress and Audit Tenure significantly affect Audit Delay. Audit Tenure contributes to improving audit efficiency and reducing Audit Delay, while Financial Distress is not a primary determinant of Audit Delay. These findings provide implications for companies and auditors in enhancing the timeliness of financial reporting.